Preparation method of heat dissipation coating, composite coating and lithium battery

By applying a high-thermal conductivity composite coating on the surface of the aluminum shell of the lithium battery, the problem of poor heat dissipation performance of large-capacity battery cells is solved, and more stable battery performance and higher safety are achieved.

CN119899574APending Publication Date: 2025-04-29SHENGHONG KINETIC ENERGY TECH (TAIZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510196688.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Large-capacity battery cells face uneven temperature problems during the heat dissipation process, resulting in unstable circulation performance of the battery cells, reduced service life, and safety hazards such as thermal runaway, fire, explosion, etc.

Method used

Using a composite coating, a high thermal conductivity heat dissipation coating is prepared by mixing hexagonal boron nitride with quercetin and combining with epoxy resin and epoxy curing agent, and applied to the surface of the aluminum shell of the lithium battery to form a composite coating to improve heat dissipation performance.

Benefits of technology

This technology effectively improves the heat dissipation performance of the battery, especially suitable for large-capacity lithium batteries greater than 280Ah, reducing the problem of uneven temperature of the battery cell and improving the service life and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899574A_ABST
    Figure CN119899574A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a heat dissipation coating, a composite coating and a lithium battery, the preparation method of the heat dissipation coating comprises the following steps: mixing hexagonal boron nitride and quercetin in absolute ethyl alcohol, and carrying out ultrasonic dispersion to obtain a mixed solution; the mixed solution is centrifugally dispersed, washed and dried, and modified hexagonal boron nitride powder is obtained; and dispersing the modified hexagonal boron nitride powder, epoxy resin and an epoxy curing agent in a solvent, and carrying out ultrasonic treatment to obtain the heat dissipation coating. By utilizing the good heat conductivity of hexagonal boron nitride, the modification effect of quercetin on hexagonal boron nitride and the characteristic that epoxy resin and epoxy hardener form a stable coating, the heat conduction efficiency is improved, and the heat of the battery cell can be quickly transferred out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to an aluminum shell coating and a lithium battery Background Art

[0002] With the booming development of the energy storage market, the market has higher and higher requirements for the capacity of energy storage systems and batteries. The "advanced" process of energy storage batteries characterized by large capacity has accelerated, and different companies have launched 300Ah+ batteries, such as 305Ah, 314Ah, 320Ah, 325Ah and other energy storage batteries of different specifications have emerged, and these large-capacity batteries have gradually replaced 280Ah energy storage batteries.

[0003] However, the development of large-capacity batteries faces severe heat dissipation challenges. Due to the high heat dissipation of high-energy-density batteries, traditional ordinary heat dissipation designs are difficult to meet their heat dissipation needs. During the battery cell cycle, heat is continuously released internally, which makes the temperature inside and on the surface of the battery cell inconsistent. This temperature difference directly affects the stability of the battery cell cycle performance, thereby reducing the service life and safety of the battery. For example, in a high-temperature environment, the chemical reaction rate of the battery is accelerated, which may cause the battery capacity to decay rapidly; while in a low-temperature environment, the internal resistance of the battery increases and the charging and discharging efficiency decreases. In addition, if the heat of the battery cell cannot be dissipated in time, when the heat accumulates to a certain extent, it may also cause thermal runaway, and even lead to serious safety accidents such as battery fire and explosion.

[0004] In response to the above problems, the existing technology has made many attempts in the design of heat dissipation structural parts. Some technologies improve the heat dissipation efficiency by adding heat sinks, but this method often increases the volume and weight of the battery, which is not in line with the development trend of lightweight and miniaturized energy storage equipment; some technologies use liquid cooling methods. Although the heat dissipation effect is better, there is a risk of leakage, and the system is complex and the cost is high. At present, there is an urgent need for a technical solution that can effectively solve the heat dissipation problem of large-capacity batteries and has the characteristics of high efficiency, simplicity, and environmental friendliness to meet the market demand for high-performance energy storage batteries. Summary of the invention

[0005] In order to overcome the defects in the prior art, the first purpose of the present invention is to provide a method for preparing a heat dissipation coating for a battery, the second purpose of the present invention is to provide a composite coating, the third purpose of the present invention is to provide a lithium battery, and the fourth purpose of the present invention is to provide an electrical device.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, a method for preparing a heat dissipation coating for a battery comprises the following steps:

[0008] The hexagonal boron nitride and quercetin are mixed in anhydrous ethanol and dispersed by ultrasonic to obtain a mixed solution;

[0009] The mixed solution is dispersed by centrifugation, washed and dried to obtain modified hexagonal boron nitride powder;

[0010] The modified hexagonal boron nitride powder, epoxy resin and epoxy curing agent are dispersed in a solvent and subjected to ultrasonic treatment to obtain a heat dissipation coating.

[0011] In the present invention, hexagonal boron nitride has good thermal conductivity. It is used as a base material and modified by adding quercetin. The -OH group in quercetin reacts with the surface of hexagonal boron nitride to enhance the dispersion stability of hexagonal boron nitride in polar solvents. The improvement in dispersion stability means that in the coating, the hexagonal boron nitride particles are more likely to contact each other and form a heat conduction path, thereby reducing the thermal resistance between the modified hexagonal boron nitride and the resin. At the same time, the -OH group in quercetin can interact with the resin matrix, promote its more uniform distribution in the resin, and further optimize the heat conduction path. The thermal conductivity of the composite coating prepared by the heat dissipation coating reaches 2.38W m -1 K -1 , which can quickly transfer the heat of the battery cell and effectively improve the heat dissipation performance of the battery, and is especially suitable for large-capacity lithium batteries greater than 280Ah.

[0012] Preferably, the hexagonal boron nitride and quercetin are mixed in anhydrous ethanol and dispersed by ultrasonic to obtain a mixed solution, comprising:

[0013] Adding hexagonal boron nitride into anhydrous ethanol and dispersing by ultrasonication to obtain a first mixed solution;

[0014] Quercetin is added into the first mixed solution, and a second mixed solution is obtained by ultrasonic dispersion.

[0015] Ultrasonic dispersion of hexagonal boron nitride and quercetin in two steps helps hexagonal boron nitride and quercetin to be more fully mixed in anhydrous ethanol and improves dispersion uniformity. This is conducive to the subsequent formation of stable modified hexagonal boron nitride powder, thereby improving the performance stability of the composite coating and ensuring the consistency of the heat dissipation effect.

[0016] Preferably, the hexagonal boron nitride and quercetin are mixed in anhydrous ethanol and dispersed by ultrasonic to obtain a mixed solution, comprising:

[0017] Adding hexagonal boron nitride into anhydrous ethanol and dispersing by ultrasonic for 15 to 25 minutes to obtain a first mixed solution;

[0018] Quercetin is added to the first mixed solution, stirred for 25 to 35 minutes, and then ultrasonically dispersed for 1.5 to 2.5 hours. During the ultrasonic treatment, it is stirred for 5 minutes at intervals of a preset time, and finally stirred for 25 to 35 minutes to obtain a second mixed solution. In the actual processing process, stirring can be performed by a magnetic stirrer. Stirring during the mixing process can improve the efficiency of solution mixing, prevent the solution from overheating, and avoid reacting too quickly. The preset time can be half an hour.

[0019] Preferably, the hexagonal boron nitride and quercetin are mixed in anhydrous ethanol at a mass ratio of (25-35):(6-10). Further preferably, the hexagonal boron nitride and quercetin are mixed in anhydrous ethanol at a mass ratio of 30:8.

[0020] Hexagonal boron nitride is added to anhydrous ethanol and ultrasonically dispersed to form a first mixed solution. This step uses the energy of ultrasound to initially disperse the hexagonal boron nitride evenly in anhydrous ethanol. Then quercetin is added and stirring and ultrasonic dispersion are continued. The -OH group in quercetin can interact with the surface of hexagonal boron nitride and enhance the dispersion stability of hexagonal boron nitride in anhydrous ethanol by non-covalent modification. Mixing at a specific mass ratio (30:8) can ensure that the two fully interact with each other and optimize subsequent performance.

[0021] Preferably, the mixed solution is centrifugally dispersed, washed and dried to obtain modified hexagonal boron nitride powder, comprising:

[0022] The second mixed solution is dispersed by centrifugation to obtain a crude product;

[0023] The crude product is washed with anhydrous ethanol for at least three times and dried to obtain modified hexagonal boron nitride powder.

[0024] The mixed solution is centrifuged to separate the modified hexagonal boron nitride from other impurities in the solution to obtain a crude product. The crude product is washed with anhydrous ethanol for multiple times to further remove residual impurities and ensure product purity. The modified hexagonal boron nitride powder is obtained by drying, which provides a pure key raw material for the subsequent preparation of heat dissipation coatings.

[0025] Preferably, the modified hexagonal boron nitride powder, epoxy resin and epoxy curing agent are dispersed in a solvent and subjected to ultrasonic treatment to obtain the heat dissipation coating, comprising:

[0026] The modified hexagonal boron nitride powder is added into ethanol and subjected to ultrasonic treatment to obtain a modified hexagonal boron nitride-ethanol dispersion;

[0027] The epoxy resin and epoxy curing agent are added into the modified hexagonal boron nitride-ethanol dispersion, and the heat dissipation coating is obtained by ultrasonic treatment;

[0028] Among them, the mass ratio of modified hexagonal boron nitride powder, epoxy resin and epoxy curing agent is (0.8-1.2):(0.8-1.2):(0.4-0.6).

[0029] In a second aspect, a composite coating is provided, wherein the composite coating is formed by coating the heat dissipation coating prepared by the above-mentioned preparation method of the heat dissipation coating on the surface of a battery aluminum shell and curing the coating.

[0030] Preferably, the absolute value of the Zeta potential of the composite coating is ≥20 mV. Zeta potential, also known as electrokinetic potential, refers to the potential difference between the shear plane (sliding plane) and the bulk of the solution. It is an important indicator for characterizing the stability of a colloidal dispersion system.

[0031] In a third aspect, a lithium battery comprises a battery core and an aluminum shell wrapped around the battery core, wherein the surface of the aluminum shell is provided with the above-mentioned composite coating.

[0032] A fourth aspect provides an electrical device, comprising the lithium battery described above.

[0033] The present invention solves the heat dissipation problem of large-capacity battery cells by preparing a specific heat dissipation coating and applying it to the aluminum shell of a lithium battery. By utilizing the good thermal conductivity of hexagonal boron nitride, the modification effect of quercetin on hexagonal boron nitride, and the characteristics of epoxy resin and epoxy curing agent forming a stable coating, the heat conduction efficiency is improved and the heat of the battery cell is quickly transferred out.

[0034] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0035] Hexagonal boron nitride has good thermal conductivity. It is used as a base material and modified by adding quercetin. The -OH group in quercetin reacts with the surface of hexagonal boron nitride to enhance the dispersion stability of hexagonal boron nitride in polar solvents. The improvement in dispersion stability means that in the coating, the hexagonal boron nitride particles are more likely to contact each other and form a heat conduction path, thereby reducing the thermal resistance between the modified hexagonal boron nitride and the resin. At the same time, the -OH group in quercetin can interact with the resin matrix, promote its more uniform distribution in the resin, and further optimize the heat conduction path. The thermal conductivity of the composite coating prepared by the heat dissipation coating reaches 2.38W m -1 K -1 , which can quickly transfer the heat of the battery cell and effectively improve the heat dissipation performance of the battery, and is especially suitable for large-capacity lithium batteries greater than 280Ah.

[0036] In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are specifically cited below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 It is the Fourier transform infrared spectra of the coatings in Example 1 and Comparative Examples 1 and 2 of the present invention.

[0039] Figure 2 This is the XPS full spectrum scan of the sample in Example 1. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Embodiment 1:

[0042] A method for preparing a heat dissipation coating, wherein the heat dissipation coating is applied to a battery housing, and the preparation method comprises the following steps:

[0043] 3.0 g of hexagonal boron nitride was added to a beaker containing 400 ml of anhydrous ethanol, and subjected to ultrasonic dispersion treatment for 20 min until the hexagonal boron nitride was completely dispersed in the anhydrous ethanol to obtain a first mixed solution. The ultrasonic power sets conventional solution treatment parameters, the purpose of which is to disperse the hexagonal boron nitride in the anhydrous ethanol.

[0044] 0.8 g of quercetin was added to the first mixed solution and stirred with a magnetic stirrer for 30 minutes to ensure that the quercetin was completely dissolved. Then, the mixed solution was placed in an ultrasonic cleaner and ultrasonicated for 2 hours. During the ultrasonic process, the magnetic stirrer was required to stir for 5 minutes every half an hour. After the ultrasonic treatment, the magnetic stirrer was required to stir again for 30 minutes to obtain the second mixed solution. The amount of anhydrous ethanol used must ensure that the hexagonal boron nitride and quercetin are fully dispersed. If the amount of solvent is insufficient, it will cause particle agglomeration and reduce the modification effect; too much solvent will increase the subsequent drying cost.

[0045] The second mixed solution is centrifugally dispersed to obtain a crude product, which is washed at least three times with anhydrous ethanol and then dried in a freeze dryer to obtain a light yellow powder, i.e., modified hexagonal boron nitride powder. The parameters of the centrifugal dispersion are set as conventional solution processing parameters, in order to achieve a dispersion effect and obtain a crude product.

[0046] 5 g of modified hexagonal boron nitride powder was dispersed in 50 ml of ethanol solution and ultrasonicated for 2 h to obtain a modified hexagonal boron nitride-ethanol dispersion.

[0047] 5 g of epoxy resin and 2.5 g of epoxy curing agent were added to the modified hexagonal boron nitride-ethanol dispersion, and ultrasonicated for 2 h to ensure that the modified hexagonal boron nitride was evenly dispersed in the epoxy resin to prepare a heat dissipation coating.

[0048] This embodiment 1 also provides a composite coating prepared from the above heat dissipation coating. The preparation method of the composite coating includes:

[0049] The heat dissipation coating is evenly coated on the surface of the aluminum shell by a glass rod using a rod coating method. The parameters in the coating process are set the same as the existing processing. Then it is placed at room temperature for 24 hours and then dried in an oven at 60° C. for 6 hours to obtain a composite coating covering the surface of the aluminum shell. The absolute value of the Zeta potential of the composite coating is ≥20mV.

[0050] This embodiment 1 also provides a lithium battery, which includes a battery core and an aluminum shell wrapped around the battery core, and the surface of the aluminum shell is provided with the above-mentioned composite coating.

[0051] Comparative Example 1:

[0052] A method for preparing a heat dissipation coating, wherein the heat dissipation coating is applied to a battery housing, and the preparation method comprises the following steps:

[0053] 3.0 g of hexagonal boron nitride was added into a beaker containing 400 ml of anhydrous ethanol, and subjected to ultrasonic dispersion treatment for 20 min until the hexagonal boron nitride was completely dispersed in the anhydrous ethanol to obtain a first mixed solution.

[0054] 0.8 g of quercetin was added to the first mixed solution and stirred with a magnetic stirrer for 30 min to ensure that the quercetin was completely dissolved. Then, the mixed solution was placed in an ultrasonic cleaner and ultrasonicated for 2 h. During the ultrasonic process, the magnetic stirrer was stirred for 5 min every half an hour. After the ultrasonic treatment, the magnetic stirrer was stirred again for 30 min to obtain a second mixed solution.

[0055] The second mixed solution is dispersed by centrifugation to obtain a crude product, and the crude product is washed with anhydrous ethanol for at least three times, and then dried in a freeze dryer to obtain a light yellow powder, namely, modified hexagonal boron nitride powder.

[0056] 5 g of modified hexagonal boron nitride powder was dispersed in 50 ml of ethanol solution and ultrasonicated for 2 h to obtain a modified hexagonal boron nitride-ethanol dispersion.

[0057] 2.5 g of epoxy resin and 5 g of epoxy curing agent were added to the modified hexagonal boron nitride-ethanol dispersion, and ultrasonic treatment was performed for 2 h to ensure that the modified hexagonal boron nitride was uniformly dispersed in the epoxy resin to prepare a heat dissipation coating.

[0058] This comparative example 1 also provides a composite coating prepared from the above heat dissipation coating. The preparation method of the composite coating comprises:

[0059] The heat dissipation coating is evenly coated on the surface of the aluminum shell by a glass rod using a rod coating method, and then placed at room temperature for 24 hours and then dried in an oven at 60° C. for 6 hours to obtain a composite coating covering the surface of the aluminum shell.

[0060] This comparative example 1 also provides a lithium battery, which includes a battery core and an aluminum shell wrapped around the battery core, and the surface of the aluminum shell is provided with the above-mentioned composite coating.

[0061] Comparative Example 2:

[0062] A method for preparing a heat dissipation coating, wherein the heat dissipation coating is applied to a battery housing, and the preparation method comprises the following steps:

[0063] 3.0 g of hexagonal boron nitride was added into a beaker containing 400 ml of anhydrous ethanol, and subjected to ultrasonic dispersion treatment for 20 min until the hexagonal boron nitride was completely dispersed in the ethanol to obtain a first mixed solution.

[0064] 0.1 g of quercetin was added to the first mixed solution and stirred with a magnetic stirrer for 30 min to ensure that the quercetin was completely dissolved. Then, the mixed solution was placed in an ultrasonic cleaner and ultrasonicated for 2 h. During the ultrasonic process, the magnetic stirrer was stirred for 5 min every half an hour. After the ultrasonic treatment, the magnetic stirrer was stirred again for 30 min to obtain a second mixed solution.

[0065] The second mixed solution is dispersed by centrifugation to obtain a crude product, and the crude product is washed with anhydrous ethanol for at least three times, and then dried in a freeze dryer to obtain a light yellow powder, namely, modified hexagonal boron nitride powder.

[0066] 5 g of modified hexagonal boron nitride powder was dispersed in 50 ml of ethanol solution and ultrasonicated for 2 h to obtain a modified hexagonal boron nitride-ethanol dispersion.

[0067] 5 g of epoxy resin and 2.5 g of epoxy curing agent were added to the modified hexagonal boron nitride-ethanol dispersion, and ultrasonicated for 2 h to ensure that the modified hexagonal boron nitride was evenly dispersed in the epoxy resin to prepare a heat dissipation coating.

[0068] This comparative example 2 also provides a composite coating prepared from the above heat dissipation coating. The preparation method of the composite coating comprises:

[0069] The heat dissipation coating is evenly coated on the surface of the aluminum shell by a glass rod using a rod coating method, and then placed at room temperature for 24 hours and then dried in an oven at 60° C. for 6 hours to obtain a composite coating covering the surface of the aluminum shell.

[0070] This comparative example 2 also provides a lithium battery, which includes a battery core and an aluminum shell wrapped around the battery core, and the surface of the aluminum shell is provided with the above-mentioned composite coating.

[0071] The heat dissipation coatings prepared in Example 1 and Comparative Examples 1 and 2 and directly purchased epoxy resins, composite coatings and lithium batteries were tested as follows:

[0072] 1. Dispersion stability test

[0073] To determine the dispersion stability of the composite coating, the Zeta potential of the coating dispersion solution was measured using a nanoparticle size and Zeta potential analyzer (Zetas i zer Nano ZS). At the same time, the corresponding particle size distribution was also measured. Before the test, the sample was ultrasonically dispersed in deionized water until the system was slightly transparent. The dispersion stability can also be observed by monitoring the changes in the coating dispersion solution over time. A certain amount of the coating dispersion solution was dispersed in ethanol and a xylene / n-butanol mixed solvent, respectively, and the dispersion solution was observed every 6 or 12 hours to record whether precipitation, stratification or other phenomena occurred.

[0074] 2. Thermal conductivity test

[0075] Laser flash analysis (LFA) is used to measure thermal conductivity. Laser flash analysis uses laser pulses to generate high-intensity flashes to excite molecules or atoms in the sample. By monitoring the various responses of the sample after being excited by the laser flash, such as the changes in the emitted fluorescence and the generated free radicals over time, various information about the sample's structure, kinetic process, reaction mechanism, etc. can be obtained. The test sample is evenly cut into a size of approximately 10 mm × 10 mm × 1 mm. The instrument used is the LFA467 laser thermal conductivity analyzer produced by NETZSCH, Germany. The thermal diffusion coefficient (α, mm 2 / Second).

[0076] 3. Thermal stability test

[0077] The STA449F5 synchronous thermal analyzer produced by NETZSCH in Germany was used to measure the thermal weight loss curve of the sample by combining thermogravimetric analysis with differential scanning calorimetry (TG-DSC). The test temperature range was from room temperature to 800°C, the heating rate was 10°C / min, and the test environment was controlled in a nitrogen atmosphere.

[0078] 4. Corrosion resistance test

[0079] A 3.5% (mass fraction) NaCl solution immersion test was used to explore the effect on the corrosion resistance of the composite coating.

[0080] 5. Fourier Transform Infrared and XPS

[0081] The functional group types of the samples were characterized by Fourier transform infrared (FT-IR) spectroscopy. X-ray photoelectron spectroscopy (XPS) analysis was performed to analyze the elemental composition and content. Figure 1 , 2 shown.

[0082]

[0083] Fourier transform infrared spectrum of hexagonal boron nitride, 1380 and 800 cm -1 The characteristic absorption peaks at 3400cm correspond to the stretching vibration of BN and the bending vibration of BNB. -1 The peak at 3400cm should be the characteristic peak of -OH, which comes from the -OH group remaining in the preparation process of hexagonal boron nitride. -1 The strong peak at about 1787cm corresponds to the characteristic absorption peak of -OH. -1 The characteristic absorption band at 1600cm is attributed to the C=O stretching vibration of the carboxyl group. -1 The peaks at about 1106 and 976 cm are due to the C=C stretching vibration of the aromatic ring. -1 The two peaks at are attributed to the asymmetric and symmetric stretching vibrations of COC, respectively. Comparing hexagonal boron nitride with quercetin, it can be observed that after modification, the characteristic absorption peak of the -OH group is significantly enhanced, which is attributed to the quercetin adsorbed on the surface of hexagonal boron nitride. In addition, some characteristic absorption peaks of quercetin exist in the Fourier transform infrared spectrum of modified hexagonal boron nitride, and no new characteristic peaks appear.

[0084] The full XPS spectrum scan shows strong signals of B, C, N and O elements, proving that these atoms exist in the modified hexagonal boron nitride. In the XPS spectrum of C1s, the five adsorption bands at 283.6, 284.5, 285.1, 286.3 and 288.3 eV were identified as CO, C-0-C, CC, C=0 and C=C, respectively

[29] . As for O1s, the three characteristic bands at 529.6, 531.3 and 532.0 eV are C-0, C-0-C and CO, respectively, which should come from quercetin. The XPS spectrum of N1s is fitted with three characteristic peaks, namely 399.2 (NC), 400.3 (NB) and 401.5 eV (NO). The formation of NC and NO bonds indicates that there is an interaction between quercetin and hexagonal boron nitride. In addition, the obvious B1s peak at 190.3 eV is due to the BN bond. These preliminary results indicate that quercetin was successfully adsorbed on the surface of hexagonal boron nitride by a non-covalent method to obtain a new type of hexagonal boron nitride, and no chemical reaction occurred between quercetin and hexagonal boron nitride during the modification process.

[0085] Through the thermal stability analysis data, it can be concluded that the temperature at which the modified hexagonal boron nitride / epoxy resin composite coating begins to decompose thermally is 310°C. It has the strongest heat resistance stability and at 800°C, the weight loss is only 5%, which can meet the needs of continuous and rapid heat conduction when the battery cell has thermal runaway.

[0086] Zeta potential and coating dispersibility results clearly show that the dispersion stability of the modified hexagonal boron nitride / epoxy composite coating has been significantly improved, and its sedimentation rate is significantly lower than that of hexagonal boron nitride or epoxy composite coating. This enhancement in dispersion stability can be attributed to the presence of -OH groups in quercetin. These groups can form hydrogen bonds with ethanol, thereby enhancing the interaction. Therefore, compared with hexagonal boron nitride or epoxy composite coatings, the modified hexagonal boron nitride / epoxy composite coating shows better dispersibility in polar solvents such as ethanol.

[0087] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A method for preparing a heat dissipation coating, wherein the heat dissipation coating is applied to a battery housing, characterized in that: The following steps are involved: The hexagonal boron nitride and quercetin are mixed in anhydrous ethanol and dispersed by ultrasonic to obtain a mixed solution; The mixed solution is dispersed by centrifugation, washed and dried to obtain modified hexagonal boron nitride powder; The modified hexagonal boron nitride powder, epoxy resin and epoxy curing agent are dispersed in a solvent and subjected to ultrasonic treatment to obtain a heat dissipation coating.

2. The method for preparing the heat dissipation coating according to claim 1, characterized in that: The hexagonal boron nitride and quercetin are mixed in anhydrous ethanol and dispersed by ultrasonic to obtain a mixed solution, comprising: Adding hexagonal boron nitride into anhydrous ethanol and dispersing by ultrasonication to obtain a first mixed solution; Quercetin is added into the first mixed solution, and a second mixed solution is obtained by ultrasonic dispersion.

3. The method for preparing the heat dissipation coating according to claim 2, characterized in that: The hexagonal boron nitride and quercetin are mixed in anhydrous ethanol and dispersed by ultrasonic to obtain a mixed solution, comprising: Adding hexagonal boron nitride into anhydrous ethanol and dispersing by ultrasonic for 15 to 25 minutes to obtain a first mixed solution; Quercetin was added to the first mixed solution, stirred for 25 to 35 minutes, and then ultrasonically dispersed for 1.5 to 2.5 hours. During the ultrasonic treatment, the mixture was stirred for 5 minutes at intervals of a preset time, and finally stirred for 25 to 35 minutes to obtain a second mixed solution.

4. The method for preparing the heat dissipation coating according to claim 2, characterized in that: The hexagonal boron nitride and quercetin are mixed in anhydrous ethanol at a mass ratio of (25-35):(6-10).

5. The method for preparing the heat dissipation coating according to claim 4, characterized in that: The hexagonal boron nitride and quercetin are mixed in anhydrous ethanol at a mass ratio of 30:

8.

6. The method for preparing the heat dissipation coating according to claim 2, characterized in that: The mixed solution is centrifugally dispersed, washed and dried to obtain modified hexagonal boron nitride powder, comprising: The second mixed solution is dispersed by centrifugation to obtain a crude product; The crude product is washed with anhydrous ethanol for at least three times and dried to obtain modified hexagonal boron nitride powder.

7. The method for preparing the heat dissipation coating according to claim 1, characterized in that: The modified hexagonal boron nitride powder, epoxy resin and epoxy curing agent are dispersed in a solvent and subjected to ultrasonic treatment to obtain a heat dissipation coating, comprising: The modified hexagonal boron nitride powder is added into ethanol and subjected to ultrasonic treatment to obtain a modified hexagonal boron nitride-ethanol dispersion; The epoxy resin and epoxy curing agent are added into the modified hexagonal boron nitride-ethanol dispersion, and the heat dissipation coating is obtained by ultrasonic treatment; Among them, the mass ratio of modified hexagonal boron nitride powder, epoxy resin and epoxy curing agent is (0.8-1.2):(0.8-1.2):(0.4-0.6).

8. A composite coating, wherein the composite coating is formed by coating the heat dissipation coating prepared by the method for preparing the heat dissipation coating according to any one of claims 1 to 6 on the surface of a battery aluminum shell and curing the coating.

9. The composite coating according to claim 7, characterized in that: The absolute value of the Zeta potential of the composite coating is ≥20mV.

10. A lithium battery, characterized in that: It comprises a battery core and an aluminum shell wrapped around the battery core, wherein the surface of the aluminum shell is provided with the composite coating according to any one of claims 7 to 8.